Biologically important areas II for cetaceans in U.S. and adjacent waters - Arctic region - Clarke, Janet T.; Ferguson, Megan C.; Brower, Amelia A.; Fujioka, Ei; Deland, Sarah (Frontiers in Marine Science, 2023)
We delineated and scored Biologically Important Areas (BIAs) in the Arctic region. The Arctic region extends from the Bering Strait to the Chukchi Sea, Beaufort Sea, Amundsen Gulf, and Viscount Melville Sound. This NOAA-led effort uses structured elicitation principles to build upon the first version of NOAA BIAs (BIA I) for cetaceans. In addition to narratives, maps, and metadata tables, BIA II products incorporated a scoring and labeling system to improve their utility and interpretability. BIAs are compilations of the best available science and have no inherent regulatory authority. They have been used by NOAA, other federal agencies, and the public to support marine spatial planning and marine mammal impact assessments, and to inform the development of conservation measures for cetaceans. Supporting evidence for Arctic BIA II came from data derived from aerial-, land-, and vessel-based surveys; satellite telemetry; passive acoustic monitoring; Indigenous knowledge; photo-identification; aboriginal subsistence harvests, including catch and sighting locations and stomach contents; and prey studies. BIAs were identified for bowhead (Balaena mysticetus), gray (Eschrichtius robustus), humpback (Megaptera novaeangliae), fin (Balaenoptera physalus), and beluga (Delphinapterus leucas) whales. In total, 44 BIAs were delineated and scored for the Arctic, including 12 reproduction, 24 feeding, and 8 migration BIAs. BIAs were identified in all months except January-March. Fifteen candidate areas did not have sufficient information to delineate as BIAs and were added to a watch list for future consideration in the BIA process. Some BIAs were transboundary between the Arctic region and the Aleutian Islands-Bering Sea region. Several BIAs were transnational, extending into territorial waters of Russia (in the Chukchi Sea) and Canada (in the Beaufort Sea), and a few BIAs were delineated in international waters.